Cannulation for Neonatal and Pediatric Extracorporeal Membrane Oxygenation for Cardiac Support - Harvey, Chris (Frontiers in Pediatrics, 2018)
The use of extracorporeal membrane oxygenation (ECMO) has increased over recent years providing respiratory and cardiac support. Optimal cannula placement is essential for successful patient outcomes. Multiple cannulation strategies may be employed depending on the age/weight of the patient and their underlying condition. This article discusses cannulation technique focusing on the cannulation of pediatric and neonatal patients for cardiac support on ECMO.